2015
DOI: 10.1111/1475-6773.12301
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy or Advanced Imaging as First Management Strategy Following a New Consultation for Low Back Pain in Primary Care: Associations with Future Health Care Utilization and Charges

Abstract: Objective. Compare health care utilization and charges for low-back-pain (LBP) patients receiving advanced imaging or physical therapy as a first management strategy following a new primary care consultation. Data Source. Electronic medical record (EMR) and insurance claims data. Study Design. Retrospective analysis of propensity-matched groups. Data Collection/Extraction. Claims and EMR data were used. Utilization and LBP-related charges over a 1-year period were extracted from claims data. Principal Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 49 publications
(48 reference statements)
2
44
1
Order By: Relevance
“…37 So although it is reasonable that women represented a larger portion of participants in our study, caution is recommended in generalizing the results to male Medicaid recipients as management strategies are known to differ for men versus women. 9,38 There are some other limitations that must be considered when reviewing these results. Our findings are ones of association rather than causation limiting the ability to direct change in current practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 So although it is reasonable that women represented a larger portion of participants in our study, caution is recommended in generalizing the results to male Medicaid recipients as management strategies are known to differ for men versus women. 9,38 There are some other limitations that must be considered when reviewing these results. Our findings are ones of association rather than causation limiting the ability to direct change in current practice.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In particular, PT early in the management of LBP is associated with reductions in subsequent health care utilization and LBPrelated costs. [7][8][9] Studies supporting PT early in the management of LBP have not examined the frequency with which PT was recommended, only the frequency with which it was received. The proportion of patients receiving early PT is low, between 7% and 20% 7,8,10 , but the proportion of patients referred is not known.…”
mentioning
confidence: 99%
“…Therefore, nurses and other health-care clinicians should be focusing on preventive strategies to reduce PLBP occurrence prior to the third decade and throughout the adult life span. This imperative may entail greater attention given to promoting evidence-based health behavior strategies to maintain musculoskeletal functioning, which include posture/body mechanics, musculoskeletal conditioning, and core strengthening exercises (Fritz et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…5,7,8,15,16 For example, Gellhorn and colleagues 5 showed that among Medicare beneficiaries with low back pain, early receipt of PT was associated with reduced downstream healthcare costs including greater than 50% reduced odds of surgery, lumbosacral injections and primary care visits in the next year. In addition, recent research reported similar functional outcomes among patients with lumbar spinal stenosis who were randomized to PT or surgical decompression, although a large number of patients randomized to PT eventually crossed over to have surgery.…”
Section: Discussionmentioning
confidence: 99%